Phytochemical Screening, Relationship of Total Phenolic with Antioxidant Activity Of Ethanol and Methanol Extracts of Kesambi (Schleichera oleosa (Lour.) Oken) Bark - Nur Alim; Tahirah Hasan; Rusman Rusman; Jasmiadi Jasmiadi; Zulfitri Zulfitri (Sam Ratulangi University, 2022)
Phenolic content has a role in antioxidant activity. The higher the phenolic content of a test sample, the higher the antioxidant activity, which is indicated by a smaller IC50 value. Methanol and 70% ethanol are solvents that have been proven to be widely used to extract total plant phenolic compounds. This study aims to determine the phytochemical content and the relationship of total phenolic content with antioxidant activity of ethanol and methanol extract of Schleichera oleosa (Lour.) Oken) bark using UV-Vis spectrophotometry. Schleichera oleosa (Lour.) Oken was extracted by maceration using 70% ethanol and methanol as solvent. Qualitative analysis of phytochemical compounds using specific reagents, analysis of total phenolic content, and antioxidant activity test using the DPPH method using UV-Vis spectrophotometry at 764 nm and 515 nm, respectively. The results of the qualitative test showed that the ethanol and the methanol extract was positive for alkaloids, flavonoids, and phenolics. The results of the analysis of total phenolic content and antioxidant activity showed that the 70% ethanol extract had a total phenolic content of 7.6829 mg gallic acid equivalent/g with IC50 28.5240 ppm and the methanol extract had a total phenolic content of 9.2057 mg gallic acid equivalent/g with IC50 1.6191 ppm. From these results, it was concluded that the higher the total phenolic content, the higher the antioxidant activity.Keywords: Antioxidant; Schlechera oleosa (Lour.) Oken.; total phenolic Skrining Fitokimia dan Hubungan Kadar Fenolik Total dengan Aktivitas Antioksidan Ekstrak Etanol dan Metanol Kulit Batang Kesambi (Schleichera oleosa (Lour.) Oken)ABSTRAKKadar fenolik memiliki peran terhadap aktivitas antioksidan. Semakin tinggi kadar fenolik suatu sampel uji maka aktivitas antioksidannya juga semakin tinggi, yang ditunjukkan dengan nilai IC50 yang lebih kecil. Pelarut metanol dan etanol 70% merupakan pelarut yang telah terbukti banyak digunakan untuk menarik senyawa fenolik total tanaman. Penelitian ini bertujuan untuk menentukan kandungan fitokimia, hubungan kadar fenolik total dengan aktivitas antioksidan ekstrak etanol dan ekstrak metanol kulit batang kesambi (Schleichera oleosa (Lour.) Oken) menggunakan spektrofotometri UV-Vis. Kulit batang kesambi (Schleichera oleosa (Lour.) Oken) diekstraksi dengan cara maserasi menggunakan pelarut etanol 70% dan pelarut metanol. Analisis kualitatif senyawa fitokimia menggunakan pereaksi spesifik, analisis kadar fenolik total dan uji aktivitas antioksidan dengan metode DPPH menggunakan spektrofotometri UV-Vis masing-masing pada panjang gelombang 764 nm dan 515 nm. Hasil uji kualitatif menunjukkan bahwa ekstrak etanol dan ekstrak metanol kulit batang kesambi (Schleichera oleosa (Lour.) Oken) positif mengandung alkaloid, flavonoid dan fenolik. Hasil analisis kadar fenolik total dan uji aktivitas antioksidan menunjukkan bahwa ekstrak etanol 70% memiliki kadar fenolik total sebesar 7,6829 mgGAE/g ekstrak dengan nilai IC50 sebesar 28,5240 ppm dan esktrak metanol memiliki kadar fenolik total sebesar 9,2057 mgGAE/g ekstrak dengan nilai IC50 sebesar 1,6191 ppm. Dari hal tersebut disimpulkan bahwa semakin tinggi kadar fenolik total maka semakin tinggi pula aktivitas antioksidannya.Kata kunci: Antioksidan; fenolik total; Schlechera oleosa (Lour.) Oken